Preterm infant physiological responses to music therapy: a systematic review - Ferry Liwang; Dinarda Ulf Nadobudskaya; Indah Lestari; Toto Wisnu Hendrarto (Paediatrica Indonesiana, 2018)
Background Prematurity is still the leading cause of mortality and morbidity in neonates. The premature change of the environment causes stress, which leads to hemodynamic instability. Music therapy may have a positive impact on hemodynamic parameters of preterm infants in the NICU. Objective To evaluate preterm infants’ physiological responses to music therapy in NICU setting. Methods A systematic review was performed in 12 electronic databases from March 2000–April 2018. Our review included all English language publications on parallel or crossover RCTs of music therapy versus standard care or placebo in preterm infants. The outcomes were physiological indicators [heart rate (HR), respiratory rate (RR), and oxygen saturation (SaO2)]. Risk of bias was assessed using the Revised Cochrane risk of bias tool for randomized trials (RoB 2.0). Results The search yielded 20 articles on 1,148 preterm infants of gestational age 28 and 37 weeks, who received recorded music, recorded maternal/male voice or lullaby, or live music interventions in the NICU with intensity of 30â€“76 dB. Recorded music improved all outcomes in 6, 6, and 4 of 16 studies for HR, RR, and SaO2, respectively. Seven studies used classical music as melodic elements. However, eight studies showed no significant results on all outcomes. Conclusion Despite the finding that music interventions demonstrate promising results in some studies, the variation in quality of the studies, age groups, outcome measures, as well as type and timing of the interventions across the studies make it difficult to draw overall conclusions about the effects of music in preterm infants.